Indole Alkaloids from Plants as Potential Leads for Antidepressant Drugs: A Mini Review - Hamid, Hazrulrizawati A.; Ramli, Aizi N. M.; Yusoff, Mashitah M. (Frontiers in Pharmacology, 2017)
Depression is the most common illness observed in the elderly, adults and children. Antidepressants prescribed are usually synthetic drugs and these can sometimes cause a wide range of unpleasant side effects. Current research is focussed on natural products from plants as they are a rich source of potent new drug leads. Besides Hypericum perforatum (St. John's wort), the plants studied include Passiflora incarnata L. (passion flower), Mitragyna speciosa (kratom), Piper methysticum G. Forst (kava) and Valeriana officinalis L. Harman, harmol, harmine, harmalol and harmaline are indole alkaloids isolated from P. incarnata, while mytragynine is isolated from M. speciosa. The structure of isolated compounds from P. methysticum G. Forst and V. officinalis L. contains an indole moiety. The indole moeity is related to the neurotransmitter serotonin which is widely implicated for brain function and cognition as the endogenous receptor agonist. An imbalance in serotonin levels may influence mood in a way that leads to depression. The moiety is present in a number of antidepressants already on the market. Hence, the objective of this review is to discuss bioactive compounds containing the indole moeity from plants that can serve as potent antidepressants.